Advanced Outfitting Techniques for Shipyard Development: A 2000 GT Shipbuilding Case Study - Pribadi, Triwilaswandio Wuruk; Wahidi, Sufian Imam; Aziz, Muhammad Naufal (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
The shipbuilding sector is currently facing issues due to long manufacturing schedules and delays in ship construction completion. These challenges come from national shipyards' conventional onboard outfitting process for equipment installation, which takes a lengthy time to complete. To address this issue, this study proposes implementing the advanced outfitting system (AOS) approach, which combines the zone outfitting system with the hull block construction method, in building a 2000 GT ship at PT. X in Surabaya, Indonesia. Technical analysis is performed to plan the shipbuilding process using the hull block construction method, and the efficiency of man-hours is calculated by implementing the AOS approach. The study also conducts an analysis of shipbuilding costs and the required shipyard development investment. The technical analysis shows that the AOS approach improves efficiency factors by enhancing material handling and testing activities. The AOS method has an efficiency factor of 50% for on-unit outfitting and 62% for on-block outfitting, compared to on-board outfitting. The construction of a 2000 GT ship employing the AOS approach represents a reduction of approximately 9.6% in working days and a cost-saving of approximately 4.3% when compared to the onboard outfitting method, resulting in savings of IDR 1,933,277,000 or about USD 124,175. To implement the AOS approach, an investment of IDR 3,040,776,000 or about USD 195,310 is required for construction facilities and human resources development. The return on investment is obtained after two 2000 GT ships are completed. As a result, the AOS approach can improve shipbuilding productivity by reducing construction time and costs. This study provides insights into the benefits of implementing modern shipbuilding techniques in the industry.